Increased Finger-Tapping Related Cerebellar Activation in Cervical Dystonia, Enhanced by Transcranial Stimulation: An Indicator of Compensation? - Odorfer, Thorsten M.; Homola, György A.; Reich, Martin M.; Volkmann, Jens; Zeller, Daniel (Frontiers in Neurology, 2019)
Background: Cervical dystonia is a movement disorder causing abnormal postures and movements of the head. While the exact pathophysiology of cervical dystonia has not yet been fully elucidated, a growing body of evidence points to the cerebellum as an important node. Methods: Here, we examined the impact of cerebellar interference by transcranial magnetic stimulation on finger-tapping related brain activation and neurophysiological measures of cortical excitability and inhibition in cervical dystonia and controls. Bilateral continuous theta-burst stimulation was used to modulate cerebellar cortical excitability in sixteen patients and matched healthy controls. In a functional magnetic resonance imaging arm, data were acquired during simple finger tapping before and after cerebellar stimulation. In a neurophysiological arm, assessment comprised motor-evoked potentials amplitude and cortical silent period duration. Theta-burst stimulation over the dorsal premotor cortex and sham stimulation (neurophysiological arm only) served as control conditions. Results: At baseline, finger tapping was associated with increased activation in the ipsilateral cerebellum in patients compared to controls. Following cerebellar theta-burst stimulation, this pattern was even more pronounced, along with an additional movement-related activation in the contralateral somatosensory region and angular gyrus. Baseline motor-evoked potential amplitudes were higher and cortical silent period duration shorter in patients compared to controls. After cerebellar theta-burst stimulation, cortical silent period duration increased significantly in dystonia patients. Conclusion: We conclude that in cervical dystonia, finger movements – though clinically non-dystonic – are associated with increased activation of the lateral cerebellum, possibly pointing to general motor disorganization, which remains subclinical in most body regions. Enhancement of this activation together with an increase of silent period duration by cerebellar continuous theta-burst stimulation may indicate predominant disinhibitory effects on Purkinje cells, eventually resulting in an inhibition of cerebello-thalamocortical circuits.